2021
DOI: 10.1590/1414-462x202199010328
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with transitions between frailty states among older persons in Brazil, 2006-2010

Abstract: Background Frailty is considered one of the major conditions faced by ageing societies. Little has been reported about the transitions between the different frailty states in developing countries. Objective This study aimed to identify the factors associated with transitions between frailty states between 2006 and 2010 among older adults in Brazil. Method The present investigation is part of the SABE study (Health, Well-being and Ageing). Frailty state was classified according to the Fried’s criteria (nonfra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Discrepant data were observed in a cohort study using data from Sabe, conducted in the city of São Paulo (Brazil), with a four-year follow-up of 1399 elderly people aged ≥ 60. It was found that 27.7% had pre-frailty throughout the follow-up, 48% remained non-frailty, and 1.8% transitioned to frailty (31).…”
Section: Discussionmentioning
confidence: 98%
“…Discrepant data were observed in a cohort study using data from Sabe, conducted in the city of São Paulo (Brazil), with a four-year follow-up of 1399 elderly people aged ≥ 60. It was found that 27.7% had pre-frailty throughout the follow-up, 48% remained non-frailty, and 1.8% transitioned to frailty (31).…”
Section: Discussionmentioning
confidence: 98%
“…Frailty is often characterised by weakness, fatigue, unintended weight loss, slowed motor functioning, and decreased energy levels [9]. It can be caused by a combination of various factors, including age-related physiological changes, underlying health conditions, environmental factors, and lifestyle choices [10,11]. Progressive declines in physical, mental, and social health are manifestations of frailty.…”
Section: Introductionmentioning
confidence: 99%